Motion Control Of An Aileron - Kotrlý, Michal (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2020)
This article covers a Bachelor’s thesis with an aim to design, assemble and test an electromechanical model of an aileron that would verify used control algorithms. Mainly those that mitigate force fight between actuators and reduce mechanical stress affecting lifespan of the aileron. Algorithms are implemented in a PLC which supplies power to actuators / sensors and controls the position and movement of the aileron.
Keywords: aileron; feedback control; position control; computer-controlled systems